Hybrid metal additive manufacturing: A state–of–the-art review - Pragana, J. P. M. (2022)
This paper starts from the early developments and working principles of the additive manufacturing of polymers, continues with a glimpse on the extension to metals with identification and characterization of the two most widespread technologies, and ends with an overview of the recent developments in hybrid metal additive manufacturing. Earlier classifications of hybrid manufacturing with roots on the utilization of primarily processed raw materials in the form of ingots, sheets, rods, tubes, profiles, powders and pellets are revisited in the light of the emergence of a new type of hybridization resulting from the combination of additive manufacturing with traditional manufacturing processes. Special emphasis is given to the combination of additive manufacturing with forming processes with the two-fold objective of (i) increasing the applicability domain of metal additive manufacturing and overcoming its limitations related to low productivity, metallurgical defects, rough surface quality and lack of dimensional precision, and (ii) adding flexibility and fostering new applications of traditional forming processes.